A revision of Pseudoparonella, Plumachaetas, Parachaetoceras and Lawrenceana (Collembola: Paronellidae), with description of three new species from New Caledonia - Zhang, Feng; Deharveng, Louis (Zootaxa, 2015)
The relationship of Pseudoparonella to other paronellid genera is currently unresolved. Authors have proposed different taxonomical systems for which the proposed subgeneric divisions have not been compared. We compared these genera in detail and conclude here that antennal length is a reliable diagnostic character. The antennae of species in the genera Plumachaetas and Parachaetoceras, are longer than body and bear long chaetae but are not longer than body in Pseudoparonella. The subapical chaeta on the maxillary outer lobe is another character potentially discriminant as it is pointed in Pseudoparonella but thick and blunt in Plumachaetas. The subgenus Lawrenceana is synonymised here with Plumachaetas because of long antennae. Three new species, Pseudoparonella seminigra sp. nov., Plumachaetas yoshii sp. nov., and Plumachaetas sunae sp. nov., are described from New Caledonia. Variation in colour patterns of Pseudoparonella griseocoerulea Yoshii is reported. New records of Pseudoparonella tanimbarica Yoshii & Suhardjono and Ps. shibatai Yosii, as well as a key to genera, are also provided.